CHK1-targeted therapy to deplete DNA replication-stressed, p53-deficient, hyperdiploid colorectal cancer stem cells. Issue 5 (7th April 2017) - Manic, Gwenola; Signore, Michele; Sistigu, Antonella; Russo, Giorgio; Corradi, Francesca; Siteni, Silvia; Musella, Martina; Vitale, Sara; De Angelis, Maria Laura; Pallocca, Matteo; Amoreo, Carla Azzurra; Sperati, Francesca; et al.
Abstract : Objective: Cancer stem cells (CSCs) are responsible for tumour formation and spreading, and their targeting is required for tumour eradication. There are limited therapeutic options for advanced colorectal cancer (CRC), particularly for tumours carrying RAS-activating mutations. The aim of this study was to identify novel CSC-targeting strategies. Design: To discover potential therapeutics to be clinically investigated as single agent, we performed a screening with a panel of FDA-approved or investigational drugs on primary CRC cells enriched for CSCs (CRC-SCs) isolated from 27 patients. Candidate predictive biomarkers of efficacy were identified by integrating genomic, reverse-phase protein microarray (RPPA) and cytogenetic analyses, and validated by immunostainings. DNA replication stress (RS) was increased by employing DNA replication-perturbing or polyploidising agents. Results: The drug-library screening led to the identification of LY2606368 as a potent anti-CSC agent acting in vitro and in vivo in tumour cells from a considerable number of patients (∼36%). By inhibiting checkpoint kinase (CHK)1, LY2606368 affected DNA replication in most CRC-SCs, including RAS-mutated ones, forcing them into premature, lethal mitoses. Parallel genomic, RPPA and cytogenetic analyses indicated that CRC-SCs sensitive to LY2606368 displayed signs of ongoing RS response, including the phosphorylation of RPA32 and ataxia telangiectasia mutated serine/threonine kinase (ATM). This was associated with mutation(s) in TP53 and hyperdiploidy, and made these CRC-SCs exquisitely dependent on CHK1 function. Accordingly, experimental increase of RS sensitised resistant CRC-SCs to LY2606368. Conclusions: LY2606368 selectively eliminates replication-stressed, p53-deficient and hyperdiploid CRC-SCs independently of RAS mutational status. These results provide a strong rationale for biomarker-driven clinical trials with LY2606368 in patients with CRC.